(untitled) (Research, Society and Development, 2021)
This paper proposes a quantitative and qualitative analysis about the blackout that occurred in Amapá System on November 3, 2020 and an approach to the recomposition process and its operational characteristics mentioning points for improvement either in the time of this recomposition and the amount of load served. Besides the analysis of what happened, the study seeks to evaluate the recomposition of the fluent and coordinated phase of Amapá’s electric system, to verify the actions taken by the National Electric System Operator - ONS, UHE Coaracy Nunes and Companhia de Eletricidade do Amapá - CEA for load taking at the beginning of the blackout until the total reestablishment of Amapá’s loads, To verify the criteria adopted by the CEA for load shedding during the recovery phases, discuss the unavailability of equipment at the CEA substations during the fluent recovery process and address the performance and impacts of the Regional Load Relief Scheme - ERAC during the fluent recovery process through the Coaracy Nunes HPP on November 4th, 2020, since it was observed that with the availability of transformer 2 (reserve) of 150 MVA in SE Macapá and of Generating Plant 1 - UG1 AMAPÁ in UHE Coaracy Nunes, in addition to the correct performance of ERAC in the substations of the distributor CEA, the impacts could be mitigated, especially regarding the available power and regarding the shutdowns of the Generating Units in Coaracy Nunes by underfrequency, making the fluent recomposition process more stable and affecting in a smaller scale the Amapaense society.